Emerging electrochemical and membrane-based systems to convert low-grade heat to electricity. Issue 2 (10th January 2018) - Rahimi, Mohammad; Straub, Anthony P.; Zhang, Fang; Zhu, Xiuping; Elimelech, Menachem; Gorski, Christopher A.; Logan, Bruce E.
Abstract : Low-grade heat from geothermal sources and industrial plants is a significant source of sustainable power that has great potential to be converted to electricity. Abstract : Low-grade heat from geothermal sources and industrial plants is a significant source of sustainable power that has great potential to be converted to electricity. The two main approaches that have been extensively investigated for converting low-grade heat to electrical energy, organic Rankine cycles and solid-state thermoelectrics, have not produced high power densities or been cost-effective for such applications. Newer, alternative liquid-based technologies are being developed that can be categorized by how the heat is used. Thermoelectrochemical cells (TECs), thermo-osmotic energy conversion (TOEC) systems, and thermally regenerative electrochemical cycles (TRECs) all use low-grade heat directly in a device that generates electricity. Other systems use heat sources to prepare solutions that are used in separate devices to produce electrical power. For example, low-temperature distillation methods can be used to produce solutions with large salinity differences to generate power using membrane-based systems, such as pressure-retarded osmosis (PRO) or reverse electrodialysis (RED); or highly concentrated ammonia solutions can be prepared for use in thermally regenerative batteries (TRBs). Among all these technologies, TRECs, TOEC, and TRBs show the most promise for effectively converting low-grade heat into electrical power mainly due to their high power productions and energy conversion efficiencies.